Enfrentando la teoría y la realidad en proyectos de software: aspectos backend del proyecto Qempo - Arevalo La Fuente, Alejandro Manuel Uladislao (2022)
This report will introduce the different steps in development for the Qempo Marketplace Backend project, starting from the initial proposal all the way to the current situation, lessons learned and future improvements. This project is part of a technological proposal that begins with analyzing the existing processes through the demonstration of a full technological product. The reason my report details only the backend component is because this was the area under my responsibility. The business value proposition was originally bringing consumer goods from the United States with ease. The initial tech stack was a website powered by an ecommerce software as a service named Magento. The role of the tech team that I was part of was to create a new platform for a new value proposal: bringing consumer goods from the USA through travelers. The new platform was designed from the ground up, and thus Software Engineering knowledge was essential throughout the project in order to achieve a robust, maintainable codebase. There were three versions of the software product which are correlated to a professional learning process based on acquired experience. Ordered, these three versions were: proof of concept, minimum viable product (MVP) and production server. The challenges faced as a new professional in Systems Engineering were to transform the business processes into a technological proposal, establish the requirements for said proposal and the required time frames for development, and introducing this new product to the business production environment. Besides the business requirements, establishing policies for personal data protection were required both by law and by business ethics. The final release of the new platform has demonstrated being solid, durable and flexible, however there are still recommendations for a future version.